Post-Modernist Eksperimental Mangunan School in Democratic Curriculum and Post-Pandemic Era: Is It Relevant? - Natalie, Regina Yoantika; Markus Budiraharjo (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
The Merdeka Belajar Curriculum is the national curriculum currently in use. However, alternative curricula can also develop in Indonesia. One of the schools that implements this alternative curriculum is Eksperimental Mangunan JHS, Yogyakarta, which has Mangunan pedagogy. Due to COVID-19, post-modernist schools must implement distance learning and have learning experiences with technology. A qualitative method with a semi-structured interview approach to related parties was used to obtain the required data. The Merdeka Belajar and Mangunan Pedagogy curricula are based on democratic education; the difference is that Mangunan schools provide character and environmental education. Besides, the use of technology is carried out in this school following the post-pandemic situation. However, this school does not digitalize education but continues to acclimate to the context of students' educational needs.